Rebellious State Crimmigration Enforcement and the Foreign Affairs Power - Mary Fan (Washington University Law Review, 2012)
The propriety of a new breed of state laws interfering in immigration enforcement is pending before the Supreme Court and the lower courts. These laws typically incorporate federal standards related to the criminalization of immigration (“crimmigration”), but diverge aggressively from federal enforcement policy. Enacting states argue that the legislation is merely a species of "cooperative federalism" that does not trespass upon the federal power over foreign affairs, foreign commerce, and nationality rules since the laws mirror federal standards. This Article challenges the formalist mirror theory assumptions behind the new laws and argues that inconsistent state crimmigration enforcement policy and resulting foreign affairs complications render the new spate of immigration policing laws infirm. The Article argues for the need to give due weight to statements of interest by the executive on the foreign affairs implications of rebellious state crimmigration enforcement. The Article argues that the caste-carving approach of the "attrition through enforcement" multi-front attack strategy behind the laws contravenes national immigration enforcement policy and strains foreign relations. The analysis provides a basis for distinguishing the Supreme Court‘s recent decision in Chamber of Commerce v. Whiting, which upheld a state employer licensing regulation, from the current spate of legislation pending in the courts. The distinction that makes a difference is conflict with a national enforcement policy calibrated to avoid turning suspected foreign nationals into untouchable caste-like "subjects of suspicion and abuse," thereby marring community and international relations. The analysis in the crimmigration context also enriches our understanding of what cooperative—and uncooperative—federalism enforcement means and the dangers of the phenomenon in areas of special national concern fraught with localized animosity.
Keywords: Immigration; Chamber of Commerce v. Whiting; 131 S. Ct. 1968 (2011); Federalism; Preemption